Recent Progress of RGD Modified Liposomes as Multistage Rocket Against Cancer - Sheikh, Afsana; Alhakamy, Nabil A.; Md, Shadab; Kesharwani, Prashant (Frontiers in Pharmacology, 2022)
Cancer is a life-threatening disease, contributing approximately 9.4 million deaths worldwide. To address this challenge, scientific researchers have investigated molecules that could act as speed-breakers for cancer. As an abiotic drug delivery system, liposomes can hold both hydrophilic and lipophilic drugs, which promote a controlled release, accumulate in the tumor microenvironment, and achieve elongated half-life with an enhanced safety profile. To further improve the safety and impair the off-target effect, the surface of liposomes could be modified in a way that is easily identified by cancer cells, promotes uptake, and facilitates angiogenesis. Integrins are overexpressed on cancer cells, which upon activation promote downstream cell signaling and eventually activate specific pathways, promoting cell growth, proliferation, and migration. RGD peptides are easily recognized by integrin over expressed cells. Just like a multistage rocket, ligand anchored liposomes can be selectively recognized by target cells, accumulate at the specific site, and finally, release the drug in a specific and desired way. This review highlights the role of integrin in cancer development, so gain more insights into the phenomenon of tumor initiation and survival. Since RGD is recognized by the integrin family, the fate of RGD has been demonstrated after its binding with the acceptor’s family. The role of RGD based liposomes in targeting various cancer cells is also highlighted in the paper.